An Evaluation of the Usability of a Computerized Decision Support System for Nursing Homes - Fossum, M.; Ehnfors, M.; Fruhling, A.; Ehrenberg, A. (Applied Clinical Informatics, 2011)
Background: Computerized decision support systems (CDSSs) have the potential to significantly improve the quality of nursing care of older people by enhancing the decision making of nursing personnel. Despite this potential, health care organizations have been slow to incorporate CDSSs into nursing home practices.Objective: This study describes facilitators and barriers that impact the ability of nursing personnel to effectively use a clinical CDSS for planning and treating pressure ulcers (PUs) and malnutrition and for following the suggested risk assessment guidelines for the care of nursing home residents.Methods: We employed a qualitative descriptive design using varied methods, including structured group interviews, cognitive walkthrough observations and a graphical user interface (GUI) usability evaluation. Group interviews were conducted with 25 nursing personnel from four nursing homes in southern Norway. Five nursing personnel participated in cognitive walkthrough observations and the GUI usability evaluation. Text transcripts were analyzed using qualitative content analysis.Results: Group interview participants reported that ease of use, usefulness and a supportive work environment were key facilitators of CDSS use. The barriers identified were lack of training, resistance to using computers and limited integration of the CDSS with the facility’s electronic health record (EHR) system. Key findings from the usability evaluation also identified the difficulty of using the CDSS within the EHR and the poorly designed GUI integration as barriers.Conclusion: Overall, we found disconnect between two types of nursing personnel. Those who were comfortable with computer technology reported positive feedback about the CDSS, while others expressed resistance to using the CDSS for various reasons. This study revealed that organizations must invest more resources in educating nursing personnel on the seriousness of PUs and poor nutrition in the elderly, providing specialized CDSS training and ensuring that nursing personnel have time in the workday to use the CDSS.
Keywords: Computerized; decision support system; graphical user interface evaluation; nursing homes; qualitative content analysis